2015
DOI: 10.1155/2015/247479
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Functioning, Desire, and Satisfaction in Women with TBI and Healthy Controls

Abstract: Traumatic brain injury (TBI) can substantially alter many areas of a person's life and there has been little research published regarding sexual functioning in women with TBI. Methods. A total of 58 women (29 with TBI and 29 healthy controls) from Neiva, Colombia, participated. There were no statistically significant differences between groups in sociodemographic characteristics. All 58 women completed the Sexual Quality of Life Questionnaire (SQoL), Female Sexual Functioning Index (FSFI), Sexual Desire Invent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
0
16
0
4
Order By: Relevance
“…Strizzi et al ( 2015 ), who carried out a study including patients with traumatic brain injury and healthy subjects showed that the level of sexual satisfaction among patients was 56.54 ± 16.56 and in the control group −84.64 ± 13.00. In a study by Andersson et al ( 2012 ) it was proven that sexually active women had a higher mean score in the SQOL-F scale (76.26 ± 24.19) than non-active women (44.13 ± 25.31).…”
Section: Discussionmentioning
confidence: 99%
“…Strizzi et al ( 2015 ), who carried out a study including patients with traumatic brain injury and healthy subjects showed that the level of sexual satisfaction among patients was 56.54 ± 16.56 and in the control group −84.64 ± 13.00. In a study by Andersson et al ( 2012 ) it was proven that sexually active women had a higher mean score in the SQOL-F scale (76.26 ± 24.19) than non-active women (44.13 ± 25.31).…”
Section: Discussionmentioning
confidence: 99%
“…Au total, 40 études ont été inclues dans l'analyse finale. Parmi elles, de façon non exclusive, 16 évaluaient la prévalence des DS chez les patients avec TC (3,6,10-23), 9 chez les couples ou les partenaires (24-32), 23 les facteurs associés aux DS (3,6,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)25,27,30,31,(33)(34)(35)(36)(37)(38) et seulement 4 les traitements des DS (39)(40)(41)(42).…”
Section: Sélection Des éTudesunclassified
“…Parmi les 23 études évaluant les facteurs associés aux DS, seules 9 utilisent des modèles multivariés pour déterminer l'indépendance de cette association (6,12,17,22,23,31,34,35,37) (Tableau 2). Ainsi, l'état de santé physique perçu (12), la participation sociale (35), l'âge (6,17,22,31,34,37), la gravité du TC (17,23,35), le délai d'évolution (6,34), la dépression (34,37), l'anxiété (37)…”
Section: Facteurs Associés Aux Dsunclassified
See 1 more Smart Citation
“…Greater sexual dysfunction among women (43%) compared to men (31%) has been reported in the general population. [ 7 ] The prevalence of sexual dysfunction during pregnancy has been reported to be 46.6% in the first trimester, 34.4% in the second trimester, and 73.3% in the third trimester[ 8 9 10 ] Sexual dysfunction can affect physical and psychological health status and well-being and also quality of life. [ 11 12 ]…”
Section: Introductionmentioning
confidence: 99%